Protocol for implementation of an evidence based parentally administered intervention for preterm infants - Rosemary White-Traut; Debra Brandon; Karen Kavanaugh; Karen Gralton; Wei Pan; Evan R. Myers; Bree Andrews; Michael Msall; Kathleen F. Norr (BMC, 2021)
Abstract Background Multi-sensory behavioral interventions for preterm infants have the potential to accelerate feeding, growth, and optimize developmental trajectories and increase parents' interactive engagement with their infants. However, few neonatal intensive care units (NICUs) provide evidence-based standardized early behavioral interventions as routine care. Lack of implementation is a major gap between research and clinical practice. H-HOPE, is a standardized behavioral intervention with an infant- directed component (Massage+) and a parent-directed component (four participatory guidance sessions that focus on preterm infants' behaviors and appropriate responses). H-HOPE has well documented efficacy. The purpose of this implementation study is to establish H-HOPE as the standard of care in 5 NICUs. Methods The study employs a Type 3 Hybrid design to simultaneously examine the implementation process and effectiveness in five NICUs. To stagger implementation across the clinical sites, we use an incomplete stepped wedge design. The five participating NICUs were purposively selected to represent different acuity levels, number of beds, locations and populations served. Our implementation strategy integrates our experience conducting H-HOPE and a well-established implementation model, the Consolidated Framework for Implementation Research (CFIR). The CFIR identifies influences (facilitators and barriers) that affect successful implementation within five domains: intervention characteristics, outer setting (the hospital and external events and stakeholders), inner setting (NICU), implementers' individual characteristics, and the implementation process. NICUs will use the CFIR process, which includes three phases: Planning and Engaging, Executing, and Reflecting and Evaluating. Because sustaining is a critical goal of implementation, we modify the CFIR implementation process by adding a final phase of Sustaining. Discussion This study builds on the CFIR, adding Sustaining H-HOPE to observe what happens when sites begin to maintain implementation without outside support, and extends its use to the NICU acute care setting. Our mixed methods analysis systematically identifies key facilitators and barriers of implementation success and effectiveness across the five domains of the CFIR. Long term benefits have not yet been studied but may include substantial health and developmental outcomes for infants, more optimal parent-child relationships, reduced stress and costs for families, and substantial indirect societal benefits including reduced health care and special education costs. Trial registration ClinicalTrials.gov registration number NCT04555590 , Registered on 8/19/2020.